Participation of Business Actors in Implementing Circular Economy on Batik Products in Kauman Batik Kampoeng, Pekalongan City - Wijaya, Muhammad Indra Hadi; Fadiyah, Tuti; Wijaya, Holi Bina; Artiningsih, Artiningsih (Universitas Diponegoro Publishing Group, Indonesia, 2024)
This research explores the application and potential of batik business actors in the implications of the circular economy (CE) model in Pekalongan, Indonesia. As a prominent cultural heritage, the batik industry is essential to the regional economy. However, conventional linear production and consumption practices have resulted in environmental challenges, resource depletion, and waste generation. By embracing CE principles that emphasize resource efficiency, waste reduction, and closed-loop systems, the batik industry in Pekalongan can develop sustainable and environmentally responsible practices. This study examines critical aspects of CE implementation, starting with community participation in the batik, drawing insights from successful CE implementation in other industries. The implementation of CE in other industries is the role of business actors in the business chain outside Kampong. This paper analyzes the potential benefits and challenges of implementing CE in the Pekalongan batik industry and the role of stakeholders in promoting circularity. By highlighting the feasibility of the CE model, the results of this research are that the level of community participation in implementing a CE has not been maximized with the potential remaining production output so that this aspect of the condition becomes a sustainable opportunity to encourage sustainable practices in the Pekalongan batik industry.